Meta-Analysis the Effects of Social Isolation and Loneliness on Cardiovascular Disease and Death in Elderly - Ayu Novita Wulandari; Bhisma Murti; Didik Tamtomo (Journal of Epidemiology and Public Health, 2023)
Background: The impact of social isolation and loneliness on health and well-being is recognized globally as a public health problem. Social isolation can be experienced at any age, especially the elderly. This study aims to analyze and estimate the influence of social isolation and loneliness on cardiovascular disease and death in the elderly.Subjects and Method: The meta-analysis was carried out according to the PRISMA flow chart and the PICO model. P: Elderly, I: Social isolation and loneliness, C: Not social isolation and not lonely, O: Cardiovascular disease and death. Search for articles in this study through databases that include PubMed, Google Scholar, Science Direct and Scopus with keywords "social isolation" AND "loneliness" AND "cardiovascular disease" AND "elderly". “Social isolation” AND “loneliness” AND “mortality” AND “elderly”. Full paper article with cohort design, adjusted Hazard Ratio for effect size, research outcome are cardiovascular disease and death. Analysis was performed using Revman 5.3.Results: There were 18 articles with cohort designs originating from America, Finland, Canada, Tai-wan, Australia, the United States, Japan, Denmark, Amsterdam, England, Sweden, Jerusalem, Europe with a total of 1,375,816 research samples. A meta-analysis of 13 cohort studies concluded that seniors who were socially isolated had a 1.23 times the risk of developing cardiovascular disease compared to those who were not socially isolated, and the effect was statistically significant (aHR= 1.23; 95% CI= 1.10 to 1.38; p= 0.003). In addition, the elderly who are socially isolated have a risk of dying 1.16 times compared to those who are not socially isolated, and this effect is statistically significant (aHR= 1.16; 95% CI= 1.07 to 1.21; p= 0.003). A meta-analysis of 13 cohort studies concluded that lonely elderly people had a 1.10 times greater risk of developing cardiovascular disease compared to lonely people, and the effect was statistically significant (aHR= 1.10; 95% CI= 1.01 to 1.20; p= 0.003). In addition, lonely elderly people have a risk of dying 1.19 times compared to being lonely, and the effect is statistically significant (aHR= 1.19; 95% CI= 1.02 to 1.39; p= 0.002).Conclusion: Social isolation and loneliness increase the risk of cardiovascular disease and death in elderly. Keywords: social isolation, loneliness, cardiovascular, death, elderly. Correspondence:Ayu Novita Wulandari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Jawa Tengah. Email: ayunovitawulandari98@gmail.com. Mobile: +6282281301325.